Is India’s Economic Growth Inclusive? A disaggregated level analysis. - Devendra Kumar (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Indian’s two decades of economic reforms has always been a matter of great interest among the development professionals, policy makers, and political leaders. To address that several studies have been conducted, however this study uses a uniquely available longitudinal data to assess how inclusive the benefits have been accrued at state level. The studies shows across states between 1993 and 2005 the real per capital income in villages which are far away from the center of economic activities (in case of this study its town) declined, however the villages which are closer to the center of economic activities their real per capital income increased. The trends persist not only for economic variables, rather that is true for health outcome, education attainment, and social networks. The debilitating effects of “distance from the center of economic activities” need to be countered through connecting outlying villages with more and better physical and social infrastructures.